Early posterior vitreous detachment is associated with LAMA5 dominant mutation. (2nd January 2019) - Napolitano, Filomena; Di Iorio, Valentina; Di Iorio, Giuseppe; Melone, Mariarosa Anna Beatrice; Gianfrancesco, Fernando; Simonelli, Francesca; Esposito, Teresa; Testa, Francesco; Sampaolo, Simone
ABSTRACT: Background: Extracellular matrix molecular components, previously linked to multisystem syndromes include collagens, fibrillins and laminins. Recently, we described a novel multisystem syndrome caused by the c.9418G>A p.(V3140M) mutation in the laminin alpha-5 ( LAMA5 ) gene, which affects connective tissues of all organs and apparatus in a three generation family. In the same family, we have also reported a myopic trait, which, however, was linked to the Prolyl 4-hydroxylase subunit alpha-2 ( P4HA2 ) gene. Results of investigation on vitreous changes and their pathogenesis are reported in the present study.Materials and Methods: Nineteen family individuals underwent complete ophthalmic examination including best-corrected visual acuity (BCVA), fundus examination, fundus photography, intraocular pressure measurement, axial length measurement using ocular biometry, Goldmann visual field examination, standard electroretinogram, SD-OCT. Segregation analysis of LAMA5 and P4HA2 mutations was performed in enrolled members.Results: The vitreous alterations fully segregated with LAMA5 mutation in both young and adult family members. Slight reduction of retinal thickness and peripheral retinal degeneration in only two patients were reported.Conclusions: In this work we showed that PVD is a common trait of LAMA5 multisystem syndrome, therefore occurring as an age-unrelated trait. We hypothesize that the p.(V3140M) mutation results in a reduction of retinal inner limiting membrane (ILM) stability, leading to a derangement in the macromolecular structure of the vitreous gel, and PVD. Further investigations will be necessary to elucidate the role of wild type and mutated LAMA5 in the pathogenesis of PVD.